Portfólio institucional da infraestrutura de pesquisa, desenvolvimento e inovação do IFMT - Lacerda, Fernanda Paiva e Silva (2020)
Since the end of the 90s, Brazil has realized the importance of promoting technological innovation and has been implementing policies aimed at C, T & I (Science, Technology and Innovation), thus considering innovation as an important factor to boost development of the national economic system. Currently, there are several forms of positive and viable interactions for carrying out activities that promote R, D & I and that encourage the sharing of the Structural Capital (SC) of Scientific and Technological Institutions (STI). The Federal Institute of Education, Science and Technology of Mato Grosso (IFMT) is an institution of basic, professional, higher education and multicampi, specialized in offering professional and technological education in different teaching modalities. In this context, however, in the IFMT there is no survey of the potential of existing laboratories, information is scarce and / or disorganized, which makes it difficult to promote knowledge and interact with IFMT and public / private institutions. This work had the general objective of mapping the structural laboratory capital of the IFMT and its subsequent publication and dissemination. A bibliographic research was carried out on scientific articles on structural capital and Brazilian legislation on innovation, later on a documentary research under the IFMT, through a questionnaire sent to all campuses to identify and characterize the laboratories and their underlying infrastructure. The platform was designed based on a survey conducted on the websites of the teaching institutions and forwarded to the computer programming team for virtual development. The responses received were tabulated using an electronic spreadsheet and analyzed to support the elaboration of tables, graphs and descriptive statistics, necessary to explain the information collected. In this sense, this work proposes a platform that will provide information about the IFMT infrastructure, equipment and technologies to the internal and external community; being able to foster the innovation potential of research infrastructures, making the productive sector more aware of the opportunities offered to improve its products and of the codevelopment of technologies and will provide elements for the evaluation and monitoring of IFMT actions aimed at expansion and recovery infrastructure of their laboratories.